2020
DOI: 10.21203/rs.3.rs-96524/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and prognostic value of cardiac troponin in elderly patients hospitalized for COVID-19

Abstract: Background: Increases in cardiac troponin (cTn) in coronavirus disease 2019 (COVID-19) have been associated with worse prognosis. Nonetheless, data about the significance of cTn in elderly subjects with COVID-19 are lacking.Methods: From a registry of consecutive patients with COVID-19 admitted to a hub hospital in Italy from 25/02/2020 to 03/07/2020, we selected those ≥60 year-old and with cTnI measured within 3 days from the molecular diagnosis of SARS-CoV-2 infection. When available, a second cTnI value wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Our finding of adverse COVID-19 outcomes associated with myocardial injury based on serial high-sensitivity cardiac troponin assessment is in line with existing evidence [21] , [22] , [23] , [24] and underscores the value of serial cardiac troponin measurements in patients with COVID-19. However, current evidence is limited by the definitions of myocardial injury employed, lack of data on serial testing and thereby dynamic cardiac troponin changes, use of inconsistent sampling intervals, and use of non-high-sensitivity assays [12] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding of adverse COVID-19 outcomes associated with myocardial injury based on serial high-sensitivity cardiac troponin assessment is in line with existing evidence [21] , [22] , [23] , [24] and underscores the value of serial cardiac troponin measurements in patients with COVID-19. However, current evidence is limited by the definitions of myocardial injury employed, lack of data on serial testing and thereby dynamic cardiac troponin changes, use of inconsistent sampling intervals, and use of non-high-sensitivity assays [12] .…”
Section: Discussionsupporting
confidence: 89%
“…Besides isolated myocardial injury or type 2 myocardial infarction, such elevations may be indicative of myocarditis or type 1 myocardial infarction and may further be associated with both increased disease severity and mortality [10] , [11] , [12] , [13] , [14] , [15] . While serial cardiac troponin testing plays crucial diagnostic and prognostic roles among patients presenting with acute-onset chest pain [16] , [17] , [18] , [19] , [20] , evolving data also suggest that serial troponin assessment may improve prognostic stratification in patients with COVID-19 [21] , [22] , [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%
“…The study involves very elderly patients (mean age is 86 y) that are the population category more involved by a severe form of COVID-19 and who most often require hospitalization. Previous studies were shown a dichotomous relationship between cTnI elevation and mortality without different rates in mortality with increasing cTnI levels ( De Marzo et al., 2021 ; García de Guadiana-Romualdo et al., 2021 ). Interestingly, in this study mortality rates increased significantly across HS-cTnT entry levels groups (group A: 18.4%; group B: 36.4%; group C: 62.0%; p <0.001).…”
Section: Discussionmentioning
confidence: 96%
“…Cardiac biomarkers ( 47 ), electrocardiography (ECG), and transthoracic echocardiography (TTE) play a pivotal role in risk stratification and early detection of cardiovascular complications, as well as to guide treatment ( 48 , 49 ). Recent evidence confirmed that cardiac biomarkers, including natriuretic peptides (NPs) and troponins, may reflect cardiovascular involvement and inflammation in COVID-19, and are strongly associated with poor prognosis and mortality ( 41 , 50 53 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 99%